Enterprise Architecture Sebagai Strategi Pengembangan Smart Village (Economic Services) Menggunakan TOGAF 9.2 - Gustriandita, Tiara Shalsabilla; Fajrillah, Asti Amalia Nur; Nurtrisha, Widyatasya Agustika (STMIK Banjarbaru, 2023)
Smart Village is a concept that adopts elements from the smart city concept, leveraging information technology. One of the Indonesian government's initiatives is to foster the development of Indonesia by empowering rural areas in pursuit of sustainable development. The selection of target areas is based on the classification of the Developing Village Index, with a focus on villages categorized as